Effect of extrusion barrel temperatures on residence time and physical properties of various flour extrudates - Lim, Sue Shan; Sulaiman, Rabiha; Sanny, Maimunah; Zainal Abedin, Nur Hanani (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2015)
The aim of this study was to evaluate the effect of barrel temperature and flour types on the residence time and physical properties of various flour extrudates. Corn flour, rice flour, corn flour with potato starch (30% w/w, d.b), and rice flour with potato starch (30%w/w, d.b) were extruded at screw speed of 75rpm, feed moisture at 25% (w/w, w.b.), barrel temperature ranging from 80°C to 140°C and die size of 1.88mm. The extrudates were dried at 50°C overnight and further analysed. Results showed that an increase in extruder barrel temperature decreased the residence time of the flours in the extruder (from 4.11-11.32min to 2.24-6.76min), but increased the expansion ratio, rehydration ratio, water absorption index, water solubility index and b value of the extrudate (p≤0.05). The extrudates had the mean residence time and physical properties of rice flour<rice flour with potato starch<corn flour with potato starch<corn flour (p≤0.05). Results showed conclude that barrel temperature and flour types showed significant effect on the residence time and physical properties of the extrudates.